Sound Similar in Surat Poets (Journal of the College of Education for Women, 2019)
This research deals with the phenomenon of a similar voice phenomenon has foundedits own laws similar and includes the following phenomenon:Azahrh aledgam: and Qdbent Tarifaoshrooth or dinaces and reflects the correlationbetween language and reading and then apply the provision in sura blessed.Phenomenon Alaalal and substitution, Two of the important acoustic phenomenon thelinguistic heritage has shown Alaalal types and the difference between him and thesubstitution then counted their applications in Sura.Similar phenomena: in name and deed shares bult causes and probability voices andsound that refrais where tilt.